Super-resolution by aperture synthesis: tilt series reconstruction in CTEM - Kirkland, A; Saxton, W; Chau, K; Tsuno, K; Kawasaki, M (1995)
A substantial resolution improvement has been achieved - increasing the continuous transfer limit from 0.23 nm to better than 0.14 nm - in a reconstruction of a set of images made with differently tilted illumination. The transfer function envelopes mean that differently tilted images effectively cover different regions of Fourier space, allowing a synthesis over an area four times that covered by conventional axial imaging with similar illumination coherence. The image processing required no more than standard series restoration filters, but new techniques were needed to establish the imaging conditions with sufficient accuracy and to identify a common origin in each image. As a route to higher resolution, the approach has in most respects considerably less stringent requirements than that of focal series restoration. © 1995 Elsevier Science B.V. All rights reserved.